Development of Test Instrument To Asses Critical Thinking Skills Using Moodle - Sinurat, Tumpal leonardo hamonangan; Sabani, Sabani ((IPER) Indonesian Physics Education Research, 2023)
This research aims to develop critical thinking based test instrument on Sound Material Using E-Learning, test the feasibility of the instrument and determine the level of students' critical thinking. The research was designed with the ADDIE Learning Design Model and was carried out at SMA Negeri 3 Medan with the subject of class XI students in the MIA program. The initial stages of this research are Analysis, the next stage is Design, then Develop stage by conducting product trials in small and large groups, and the last stage is Implement with evaluation at each step, the last stage is the distribution of instruments carried out within the scope of SMA Country 3 Medan. The results showed that the test instrument based on Critical Thinking Skills On Sound Material Using E-Learning the sound wave material developed by the researcher had met the criteria worthy of being used as a sound wave material learning outcome test instrument. The feasibility of this test instrument was based on validity and reliability tests, from validity test, from 20 questions obtained 7 valid questions. For the large group reliability test, the value of 0.72 is included in the feasible category. It can be concluded that the questions developed by researchers can be used as a measuring tool for students' cognitive knowledge and can be well received by students.